Meningkatkan Minat Belajar Siswa Pada Materi Kisah Fathu Makkah Melalui Poster Cerita Kls 4 MI Salafiyah - Wahidiyah Wahidiyah; Ahmad Fauzi (Reflection : Islamic Education Journal, 2025)
The subject of Islamic Cultural History (SKI) plays an important role in instilling Islamic historical values in students. One of the topics taught is the Story of Fathu Makkah, which describes the victory of Prophet Muhammad (PBUH) and the Muslims in conquering the city of Makkah without war. However, in the learning process of grade IV students at MI Salafiyah, it was found that students showed a lack of interest in this material due to conventional and less engaging teaching methods. This study aims to enhance students' interest in learning the Story of Fathu Makkah through the use of story posters as a teaching medium. The research method employed is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. Data were collected through observations, student learning interest questionnaires, and comprehension test results. The findings indicate that the use of story posters significantly increased students' learning interest. In the first cycle, students began to show interest in the material, although some were still less active. After improvements were made in the second cycle, there was an increase in student engagement during discussions, and their understanding of the material improved. Moreover, the students' average scores increased compared to before the intervention. The conclusion of this study is that the use of story posters can enhance students' learning interest in the Story of Fathu Makkah in grade IV at MI Salafiyah.